2017
DOI: 10.1038/s41598-017-16448-5
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies increase the levels of mitochondrial DNA in placental extracellular vesicles: Alarmin-g for preeclampsia

Abstract: The pathogenesis of preeclampsia remains unclear but placental factors are known to play a crucial role causing maternal endothelial cell dysfunction. One potential factor is placental micro- and nano- vesicles. Antiphospholipid antibodies (aPL) increase the risk of preeclampsia ten-fold, in part by damaging the mitochondria in the syncytiotrophoblast. Since mitochondrial DNA (mtDNA) is a danger- associated molecular pattern (DAMP/alarmin) that may activate endothelial cells, the aims of the current study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 70 publications
1
35
0
Order By: Relevance
“…The presence of DNA in placental EVs is important because: (1) the DNA is fetal in origin and is likely to be encapsulated and protected from circulating nucleases, increasing its potential to be used for noninvasive prenatal diagnosis; and (2) since fetal nuclear DNA is hypomethylated relative to adult nuclear DNA, this EV‐associated DNA may act as a danger‐associated molecular pattern to activate innate immune Toll‐like receptors in recipient cells. We have recently shown that mitochondrial DNA, present in placental micro‐ and nano‐EVs, activates TLR9 in endothelial cells, leading to endothelial cell activation, a hallmark of preeclampsia . In preeclampsia, an increase in DNA‐positive placental micro‐EVs in the maternal circulation has been reported …”
Section: Cargo Of Placental Extracellular Vesiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of DNA in placental EVs is important because: (1) the DNA is fetal in origin and is likely to be encapsulated and protected from circulating nucleases, increasing its potential to be used for noninvasive prenatal diagnosis; and (2) since fetal nuclear DNA is hypomethylated relative to adult nuclear DNA, this EV‐associated DNA may act as a danger‐associated molecular pattern to activate innate immune Toll‐like receptors in recipient cells. We have recently shown that mitochondrial DNA, present in placental micro‐ and nano‐EVs, activates TLR9 in endothelial cells, leading to endothelial cell activation, a hallmark of preeclampsia . In preeclampsia, an increase in DNA‐positive placental micro‐EVs in the maternal circulation has been reported …”
Section: Cargo Of Placental Extracellular Vesiclesmentioning
confidence: 99%
“…Similarly, macro‐EVs extruded by preeclamptic placentae can affect nitric oxide and calcium signaling in endothelial cells, leading to endothelial cell activation . These effects may be due to the presence of danger‐associated molecular patterns in placental EVs, such as HMGB1 or mitochondrial DNA …”
Section: Effects Of Placental Extracellular Vesicles On Endothelial Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the export of both micro-EVs and nano-EVs containing misfolded proteins may harm the maternal cells that take up these vesicles [5,49]. We have previously shown that EVs from placentae treated with antiphospholipid antibodies contain increased amounts of various danger signals including mitochondrial DNA [50] and HMGB1 [51]. The increased load of misfolded proteins delivered to endothelial cells by EVs from antiphospholipid antibody-affected placentae may be an another factor that contributes to the endothelial cell activation that is a hallmark of preeclampsia, or in maternal organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no significance of raised APA in cases of infertility and recurrent abortions, and the positive of APA is not necessarily related to early spontaneous abortion, other studies including a multicenter study of 283 pregnancies still supported that APA may increase the risk of pre‐eclampsia in part by increasing the amount of mitochondrial DNA and confirmed that APA positivity is risk factors for adverse maternal and fetal outcomes …”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%